2019
DOI: 10.1021/acs.est.8b07016
|View full text |Cite
|
Sign up to set email alerts
|

Upcycling of Spent Lithium Cobalt Oxide Cathodes from Discarded Lithium-Ion Batteries as Solid Lubricant Additive

Abstract: This work provides an alternative solution to the challenge of battery recycling via the upcycling of spent lithium cobalt oxide (LCO) as a new promising solid lubricant additive. An advanced solid lubricant mixture of graphene, Aremco binder, and recycled LCO was formulated into a spray with the use of excess volatile organic solvent. Numerous flat steel disks were spray-coated with the new lubricant formulation and naturally dried followed by curing at 180 °C. When tested on a ball-on-disk up to 230 m in dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 26 publications
(37 reference statements)
0
17
0
Order By: Relevance
“…Therefore, the cathode materials from obsolete LIBs were directly reused as a catalyst to degrade organic contaminants by a simple washing–recycling process (SI Figure S6). It was found that Mn (III) intermediate in spent battery played an important role in catalytic reaction. The result showed that Rhodamine B (Rh B) degradation rate increased from 43.7% to 98.2% with only recycled MnO 2 as the catalyst, and the catalytic activity of recycled MnO 2 was enhanced for activating peroxymonosulfate (PMS) for contaminant degradation. , In addition, Vihang P. et al provided an alternative solution to spent LiCoO 2 (LCO) battery recovery by upcycling cathode materials as a solid lubricant additive (SI Figure S6). The binder including carbon and nitrogen elements was identified as a bridge-like structure between particles, and uniform distribution of LCO across the coating was apparent from elemental mapping of cobalt.…”
Section: Other Processing Methodsmentioning
confidence: 99%
“…Therefore, the cathode materials from obsolete LIBs were directly reused as a catalyst to degrade organic contaminants by a simple washing–recycling process (SI Figure S6). It was found that Mn (III) intermediate in spent battery played an important role in catalytic reaction. The result showed that Rhodamine B (Rh B) degradation rate increased from 43.7% to 98.2% with only recycled MnO 2 as the catalyst, and the catalytic activity of recycled MnO 2 was enhanced for activating peroxymonosulfate (PMS) for contaminant degradation. , In addition, Vihang P. et al provided an alternative solution to spent LiCoO 2 (LCO) battery recovery by upcycling cathode materials as a solid lubricant additive (SI Figure S6). The binder including carbon and nitrogen elements was identified as a bridge-like structure between particles, and uniform distribution of LCO across the coating was apparent from elemental mapping of cobalt.…”
Section: Other Processing Methodsmentioning
confidence: 99%
“…Meanwhile, these brine lakes are located at limited areas of South America, and it is thereby difficult to secure the lithium supply with a certain level of independence from diverse external (e.g., political) factors. For this reason, needs for recycling lithium from spent batteries and lithium recovery from alternative sources have arisen. There have been large efforts to develop technologies for lithium recovery (into the form of concentrated lithium compounds, usually lithium carbonate) from waters containing a low concentration of Li + , with an ultimate goal of extracting lithium from seawater; the overall amount of lithium in seawater is approximately 250 billion tons, but its concentration is only 0.17 mg/L. , …”
Section: Introductionmentioning
confidence: 99%
“…20 With proper treatments, the obtained cathode can be also processed as a solid lubricant additive which reduces the coefficient of friction by 85%. 21 Furthermore, the spent cathode can be directly processed to re-generate new cathode by lots of methods including wet leaching, 22 suspension electrolysis, 23 chlorination 24 /sulfation roasting, 25 and carbothermal reduction. 26 In addition, the metal composition of the cathode is much simple which can be classified into lithium and transition metals.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, the cathode in spent LIBs can be directly employed as the catalyst for organics degradation . With proper treatments, the obtained cathode can be also processed as a solid lubricant additive which reduces the coefficient of friction by 85% . Furthermore, the spent cathode can be directly processed to re-generate new cathode by lots of methods including wet leaching, suspension electrolysis, chlorination/sulfation roasting, and carbothermal reduction .…”
Section: Introductionmentioning
confidence: 99%